Analyzing The Impact of Marketing Strategy of Dior on Brand Equity - Li, Chenxi (Transactions on Economics, Business and Management Research, 2024)
This article, based on Dior's media and marketing performance during the Paris Olympic Games, describes its marketing techniques in several scenarios. It investigates and explains techniques for improving Dior's long-term brand image and value, allowing it to preserve its position as a fashion industry leader using brand cognition and circle marketing theories. This research sought to analyze the reasons for Dior's brief increase in brand image at the conclusion of the Olympic Games and proposed three viable solutions. First, Dior worked with a sports image ambassador to boost the brand's image and awareness. Dior should continue to work with well-known figures to boost the brand's reputation, reinforce its own brand development, and continually nurture a more distinctive and original brand image. Second, Dior should increase its brand value through targeted content marketing and circle marketing techniques. Next, Dior should prioritize diversity and creativity in content marketing, pay close attention to accurate positioning in circular marketing, and establish differentiated marketing tactics to sustain its leadership and consistently increase brand value. Finally, Dior should highlight its stylish performance at the opening and closing ceremonies. To build long-term fashion leadership, Dior should combine luxury branding with art and design. This study analyzes Dior's marketing strategy in the context of the Olympics and offers recommendations for future growth.